Randomized phase III study to evaluate the value of omission of prophylactic neck dissection for stage I/II tongue cancer: Japan Clinical Oncology Group study (JCOG1601, RESPOND). (21st October 2018) - Tanaka, Kiyo; Hanai, Nobuhiro; Eba, Junko; Mizusawa, Junki; Asakage, Takahiro; Homma, Akihiro; Kiyota, Naomi; Fukuda, Haruhiko; Hayashi, Ryuichi; ,
Abstract : A randomized phase III trial evaluating the omission value for prophylactic neck dissection for stage I/II tongue cancer with 3–10 mm DOI was initiated in November 2017. Abstract: For stage I/II tongue cancer patients, it is controversial whether prophylactic neck dissection should be performed with partial glossectomy. Based on the evidence of the primary tumor's depth of invasion as a predictive factor of occult lymph node metastases and a prognostic factor of disease-free survival, randomized phase III trial was initiated in November 2017 to evaluate the omission value for prophylactic neck dissection for stage I/II tongue cancer with 3–10 mm of depth of invasion. In 5 years, 440 patients will be accrued from 28 institutions. The primary end point of the study is the overall survival, whereas the secondary end points are relapse-free survival, local relapse-free survival, proportion of unresectable relapse and of cervical lymph node relapse, post-operative function (paralysis of the accessory and facial nerves and subjective symptoms) and adverse events. This trial has been registered with the UMIN Clinical Trials Registry (registration number: UMIN000030098; http://www.umin.ac.jp/ctr/index.htm ).